What are end-users’ needs and preferences for a comprehensive e-health program for type 2 diabetes? – A qualitative user preference study - Tina Rishaug; Anne-Marie Aas; André Henriksen; Gunnar Hartvigsen; Kåre Inge Birkeland; Eirik Årsand (PLoS ONE, 2025)
Introduction Type 2 diabetes (T2D) prevalence is rising, which imposes a significant burden on individuals, healthcare systems, and economies worldwide. Lifestyle factors contribute significantly to the escalating incidence of T2D. Consequently, there is an increasing need for interventions that not only target at-risk populations for prevention but also empower individuals with T2D to achieve better self-management and possibly attain remission through sustained lifestyle modifications. Technological tools may improve health outcomes compared to traditional in-person care, and can include registration of important health parameters, provide follow-up and support, and enhance self-management. The aim of this study was to receive feedback from end-users to inform the development of a comprehensive e-health program focusing on lifestyle modification in pre-diabetes and T2D. Methods During eight focus group meetings, sixteen adults with pre-diabetes or T2D from all over Norway informed the study about needs and preferences for an e-health program, including essential functionalities and design choices. A questionnaire and paper prototyping were used to complement the discussions in the focus group meetings. Results Lack of necessary diabetes knowledge was common, and education was considered essential for improved self-management. Essential functionalities included registration and overview of several health parameters, long-term follow-up and coaching through communication platforms within the program, automatic data transfer from different devices such as blood glucose monitors and smartwatches, and educational courses. To ensure end-users’ satisfaction with the program and increase motivation for long-term usage, the participants rendered tailoring of desired functionalities and content as crucial. Conclusion Based on the findings, a list of recommendations was created, containing the most crucial functionalities and features to include when developing e-health and/or m-health tools for people with pre-diabetes and T2D. Future work should include health care personnel to explore their needs and preferences, and ways such an e-health program may enhance patient interaction without increasing workload and resource use.